Fertility in the region of the transamazonic highway II. Phosphorus fixation in Red-Yellow Podzolic and “ Terra roxa estruturada latossólica” - Dynia, José Flávio; Moreira, Gisa Nata C.; Bloise, Raphael Minotti (Pesquisa Agropecuaria Brasileira, 2014)
It was studied, under laboratory condition, the phosphorus fixation in a sandy clay loam 5011 Red- Yellow Podzolic and in a clay soil – “Terra Roxa estruturada Latossólica” (comprised in the former Reddish-Brown Lateritic Soils). In the Red-Yellow Podzolic, which showed 3 ppm of available phosphorus and 1,0 me/100 g of exchangeable aluminum, two types of incubation wore mode - with excess of water and at field capacity - using "+ CaCO3 p.a." and "—CaCO3 p.a." treatments in both cases and working with two replications for each treatment. The dosis of phosphorus applied were: 75, 150, 225 and 300 ppm. The highest percentage of fixation (40%) was reached at the lowest level (75 ppm) within 7 days for the soil at field capacity and within 3 days for the soil with excess, of water (35%). There was no difference between soil treated with CaCO3 p.a. and soil without CaCO3 P.C. The "Terra Roxa Estruturada Latossólica" showed 10 ppm of available phosphorus and no exchangeable aluminum. The test was carried out in a single series, at field capacity, with two replications for each treatment. The dosis of phosphorus applied were 13, 26, 40 and 53 ppm. The percentage of fixation held up around 80% in cii treatments, since the first day of incubation.